Effects of the P‐Selectin Antagonist Inclacumab on Myocardial Damage After Percutaneous Coronary Intervention According to Timing of Infusion: Insights From the SELECT‐ACS Trial. Issue 11 (November 2016) - Stähli, Barbara E.; Gebhard, Catherine; Duchatelle, Valérie; Cournoyer, Daniel; Petroni, Thibaut; Tanguay, Jean‐François; Robb, Stephen; Mann, Jessica; Guertin, Marie‐Claude; Wright, R. Scott; L. L'Allier, Philippe; Tardif, Jean‐Claude
Abstract : Background: The Effects of the P‐Selectin Antagonist Inclacumab on Myocardial Damage After Percutaneous Coronary Intervention for Non‐ST‐Segment Elevation Myocardial Infarction (SELECT‐ACS) trial suggested beneficial effects of inclacumab, a monoclonal antibody directed against P‐selectin, on periprocedural myocardial damage. This study evaluated the effect of inclacumab on myocardial damage according to varying time intervals between study drug infusion and percutaneous coronary intervention (PCI). Methods and Results: Patients (n=544) enrolled in the SELECT‐ACS trial and randomized to receive 1 infusion of placebo or inclacumab (5 or 20 mg/kg, administered between 1 and 24 hours before PCI) were divided according to the time interval between study drug infusion and PCI. The primary end point was the change in troponin I from baseline at 16 and 24 hours after PCI. In patients receiving inclacumab 20 mg/kg with a short (less than median) time interval between infusion and PCI, placebo‐adjusted geometric mean percent changes in troponin I, creatine kinase–myocardial band, and peak troponin I at 24 hours were −45.6% ( P =0.005), −30.7% ( P =0.01), and −37.3% ( P =0.02), respectively. No significant changes were observed in patients with a long (greater than median) time interval between infusion and PCI. Placebo‐adjusted geometric mean percent changes in troponin I and creatine kinase–myocardial band were −43.5% ( P =0.02) and −26.0% ( P =0.07), respectively, when inclacumab 20 mg/kg was administered between 1 and 3 hours before PCI, whereas the drug had no effect with longer intervals. Conclusions: Inclacumab 20 mg/kg significantly reduces myocardial damage after PCI in patients with non–ST‐segment elevation myocardial infarction, and benefits are larger when the infusion is administered <3 hours before PCI. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01327183.